Designing Elements Of An Inclusive Teacher Emancipation Model Based On Hadith From The Book Of Riyadhus Solihin: A Fuzzy Delphi Analysis - Nurul Asiah Fasehah Muhamad; Noornajihan Ja‘afar; Siti Fatimah Mohd Tawil; Norakyairee Mohd. Raus; Nur Syuhaidah Alimar Shidi; Noor Azma Mohamad Khassim; Mahfuzah Mohammed Zabidi (Hunan University, 2024)
Non-Indexed Publication